Assessment of nurses' workload in intensive care unit by use of scoring systems - Vuković, Ljiljana (Array, 2020)
Aim. To assess the level of correlation between two scoring systems: patient categorization according to the Croatian Nursing Council consensus and Nine Equivalents of Nursing Manpower Use Score (NEMS) and their ability to determine if the number of nurses working in the intensive care unit (ICU) is optimal to provide adequate nursing care, and to assess the level of correlation between the severity of patients’ illness and the level of nurses’ satisfaction with provided care. Methods. Research was performed in surgical ICU of the Clinical Department of Anesthesiology, Resuscitation and Intensive Care Medicine, University Hospital Dubrava, in the period between January 8th and April 14th, 2014. 256 patients aged 18-92 years were included in the study. Patient categorization and NEMS were calculated each day during the first 7 days of the ICU stay. NEMS was calculated using a pre-made table of variables and categorization was calculated using an electronic form included in nursing electronic patient files. Satisfaction of provided care was expressed using the Likert scale (1-5). Results. Study results have shown a moderate but significant level of correlation between the categorization and NEMS scores. Mean NEMS score during the first 7 days in the ICU was 26.93 ± 4.64 and the highest measured values were at day 4 (30.34±8.1) after which they started decreasing. Mean cumulative NEMS throughout the whole ICU stay was 269.3. According to the fact that according to NEMS scoring system one nurse can provide maximum of 45 points for 24 hours, the results have shown that a 10 bed ICU needs at least 5.98 (6) nurses to provide adequate level of care. Average categorization score was 57.83±4.29 and the highest recorded score was at day 7 (59.7±4.44). According to the categorization scoring system time needed to provide care for one 4th category patient throughout 24 hours is 10 or more hours.